Some remarks on K_0 of noncommutative tori - Chakraborty, Sayan (Mathematica Scandinavica, 2020)
Using Rieffel’s construction of projective modules over higher dimensional noncommutative tori, we construct projective modules over some continuous field of C*-algebras whose fibres are noncommutative tori. Using a result of Echterhoff et al., our construction gives generators of K_0 for all noncommutative tori.